Faktor Risiko Terjadinya Anemia pada Pasien Tuberculosis Paru dalam Fase Pengobatan - Rosidah, Umi; Auliya, Qurrotu Ayuni; Wikandari, Ririh Jatmi; Widiyanto, Santo Yoseph Didik (Poltekkes Kemenkes Semarang, 2024)
Tuberculosis lungs is disease infectious disease caused by bacteria Mycobacterium tuberculosis. Tuberculosis is still a disease become threat health Indonesian society which leads to illness , disability and death tall so that need existence mitigation. Research objectives know factor risk the occurrence of anemia in patients tuberculosis lungs in phase treatment . Study This is study retrospective analytic case control Study carried out at the Community Health Center Very Beautiful Subdistrict Genuk City of Semarang. Population all TB patients who are undergo treatment at the Community Health Center Bangetayu. Research sample This from the total population namely 34 case and control patients. The results of 34 respondents case control there is level hemoglobin in patients Tuberculosis lungs with anemia (case) as many as 17 respondents experienced decline hemoglobin levels, namely man with an average hemoglobin level of 12.2 gr/dL (7 respondents), women with The average hemoglobin level was 10.6 gr/dL (2 respondents). A total of 17 respondents non - anemic control , namely the majority is normal with type sex Woman with an average Hemoglobin level of 12.61 gr/dL (17 respondents ). Based on characteristics what kind sex male 29.41% and gender sex women 11.76%. Decrease hemoglobin levels , namely man with an average hemoglobin level of 12.2 gr/dL (5 respondents), women with average hemoglobin level 10.6 gr/dL (2 respondents). Based on characteristics of the type sex women 70.59% (24 respondents) and men 29.41% (10 respondents). Based on characteristics age category adults 64.71% (22 respondents), elderly 23.53% (8 respondents), infants and children 11.76% (4 respondents), and adolescents 0.00% (0 respondents). The results of the bivariate test of hemoglobin levels, age , and type sex there is connection between hemoglobin levels, age, and type sex to Pulmonary Tuberculosis patients in phase treatment. The most influential risk factor o to the occurrence of anemia in patients with pulmonary tuberculosis in phase treatment namely on the variables type sex that is own risk of 3,429. Next followed by variables hemoglobin levels that have risk of 0.370. Age No there is factor risk the occurrence anemia in pulmonary tuberculosis patients in phase treatment. The conclusion of this study is that hemoglobin levels and sex are risk factors for anemia in patients with pulmonary tuberculosis in the treatment phase. Anemia can affect the diagnosis, prognosis, complications, and response to tuberculosis therapy, so that tuberculosis patients can maintain nutritional intake and therapy compliance to suppress the progression of the disease.